Moderating effect of goal orientation on the relationship between academic self-efficacy, learner characteristics and learning achievement in an open distance learning (ODL) based higher education institution - Norsiah Aminudin,; Zahir Osman,; Zorah Abu Kassim,; Mohd Ezanni Jaafar, (2019)
This study focuses on factors influencing learning achievement in an Open-Distance- Learning environment of a higher education institution. This study explores the relationship between academic self-efficacy and individual learner characteristics on learning achievement (learning transfer, generalisation, and maintenance). Moreover, this study investigates the role of learner goal orientation. The objectives of the study are, first, to investigate a proposed model to represent theoretical relationship between academic self-efficacy, learner characteristics and learning achievement. Secondly, to confirm learner goal orientation moderates the relationship between learner selfefficacy and training effectiveness. The measures employed in the study are adopted from past studies; goal orientation, self-efficacy and learning achievement using a fivepoint Likert scale. The study utilised purposive sampling. Respondents are postgraduate students from Open University Malaysia (OUM). Analysis was done by using SmartPLS. Findings indicate that hypothesis were supported.